ISLAMIC VIS A VIS PANCASILA - Fauzi, Mohamad (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan)
Historical travel has proven that the process to decide Pancasila as the basic state is not difficult to struggle. It also shows how our founding fathers have sacrificed and wisely seek common ground (kalimatunsawa) on mutually agreed ideologies. As the eclecticity of the secular state and the Islamic state, Pancasila not only accentuated the spirit of democracy and Human Rights which gave space to individual freedom and attracted the role of the state to regulate it, but also placed the frame of the Believing Godhead, which is in accordance with the principle of tawhid- in Islam and humanity with dignity and justice, and social justice for all Indonesian people.And of course the basic values of Pancasila as mentioned above are not contradictory and justified in the Islamic teachings that rahmatan lil-alamin (the grace of the whole world), and not rahmatan lil-muslimin (mercy of Muslims only) exclusive or even merely rahmatan lil-madzhabiyyin (the mercy of a particular adherent of madhhab in Islam) is more exclusiveHistorical travel has proven that the process to decide Pancasila as the basic state is not difficult to struggle. It also shows how our founding fathers have sacrificed and wisely seek common ground (kalimatunsawa) on mutually agreed ideologies. As the eclecticity of the secular state and the Islamic state, Pancasila not only accentuated the spirit of democracy and Human Rights which gave space to individual freedom and attracted the role of the state to regulate it, but also placed the frame of the Believing Godhead, which is in accordance with the principle of tawhid- in Islam and humanity with dignity and justice, and social justice for all Indonesian people.And of course the basic values of Pancasila as mentioned above are not contradictory and justified in the Islamic teachings that rahmatan lil-alamin (the grace of the whole world), and not rahmatan lil-muslimin (mercy of Muslims only) exclusive or even merely rahmatan lil-madzhabiyyin (the mercy of a particular adherent of madhhab in Islam) is more exclusive